Biological evaluation of para-rubber seeds (Hevea brasiliensis) - Fetuga B L; Aveni T O; Babatunde G M; Balogun M A; Olaniyan A; Oyenuga V A
Proximate nutrient composition and mineral constituents were determined in full-fat and defatted rubber seeds. Total amino acid composition of full-fat rubber seeds, peanut and soybean meals was also determined by column chromatography for amino acids. Four experiments were conducted using 28-day old albino rats (initial weights,50-55g) with the following objectives: (i) to compare the protein quality of full-fat and defatted rubber seed meals; (ii) to test the effect of autoclaving on the protein quality of full-fat and defatted rubber seed meals; (iii) to assess the effects of hot water, dilute acid and dilute alkali extraction on the nutritive value of rubber seed and (iv) to measure responses to amino acid supplementation of both full-fat and defatted rubber seed meals.The full-fat and defatted rubber seeds had protein contents of 22.54+_ 0.52;and 36.48+-0.84;respectively and fat contents of 49.49+_ 1.54;and 8.54+_ 0.38;. Both the full-fat and defatted samples contain fairly high levels of calcium (0.48+_0.02 and 0.88+_0.05;); (0.48+_0.02 and 0.88+_0.05;); phosphorous(0.64+_0.06 and 0.94+_0.09;); potassium (0.96+_0.42 and 1.54+_0.63): iron(92.72+_11.54 and 147.45+_8.32 mg/kg) and zinc (78.46+_2.11 and 112.29+_ 4.86 mg/kg). Amino acid analysis indicated lower levels of lysine, i o-leucine, leucine phenylalanine, tyrosine, proline and glycine compared to peanut and soybean and lower methionine and cystine content compared to soybean. Poorer protein quality indices were obtainedfor both types of rubber seed compared to peanut and soybean, while the full-fat seed meal was nutritionally superior to the defatted sample. Autoclaving did not improve the nutritive indices of the rubber seed meals. Dilute acid or alkali treatment worsened rat responses, while hot water extraction resulted in nonsignificant improvements in the nutritive value. Responses to amino acid supplementation suggest that lysine and methionine are most limiting in rubber seed protein. The overall results also suggest an impairment of the nutritive value of rubber seeds by extraction with petroleum spirit.
Keywords: Biological evaluation; Defatted rubber seeds; Full-fat rubber seeds; Nutritive value; Rubber seed meal; Rubber seeds